KEADILAN HUKUM DALAM PERSPEKTIF FILSAFAT HUKUM: Up hold law institution, justice - admin, admin (JAMAK, 2014)
The effort of up hold the law in create of justice in this state is sleep. Manny presssing case show the fact, the process of justice has value, in doing his work , the up hold the law can not a s a justice holder. The judicative of reformation versus oportunism of agency.